Sistem Electroencephalogram (EEG) Untuk Analisis Sinyal Gelombang Otak Pada Pasien Depresi - Rivaldy Anggara; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Electroencephalogram (EEG) is a brain signal processing technique used to detect abnormal brain waves. EEG signal recording uses electrodes placed on the scalp. AD620 is used to obtain high input impedance. The EEG signal is amplified by transmitting the signal into the notch filter, high pass filter and low pass filter to improve the quality of the signal such as eliminating and reducing noise. EEG recording focuses on analyzing alpha waves to determine whether the subject is suffering from depression. For cases of depression, the lobes of the brain placed electrodes are the Occipital and Parietal lobes of the brain. The selection of participants in this study was based on the results of tests using the Patient Health Questionnaire-9 (PHQ-9) method. The results obtained after recording EEG are there is theta wave shaped abnormally large and abnormal alpha wave who shaped abnormally large. Keywords : Electroencephalogram, amplifier, depresi, PHQ-9